Effects of Weight Loss on Obstructive Sleep Apnea Severity. Ten-Year Results of the Sleep AHEAD Study - Kuna, Samuel T. (Am J Respir Crit Care Med, 2021)
Rationale: Weight loss is recommended to treat obstructive sleep apnea (OSA). Objectives: To determine whether the initial benefit of intensive lifestyle intervention (ILI) for weight loss on OSA severity is maintained at 10 years. Methods: Ten-year follow-up polysomnograms of 134 of 264 adults in Sleep AHEAD (Action for Health in Diabetes) with overweight/obesity, type 2 diabetes mellitus, and OSA were randomized to ILI for weight loss or diabetes support and education (DSE). Measurements and Main Results: Change in apnea–hypopnea index (AHI) was measured. Mean ± SE weight losses of ILI participants of 10.7 ± 0.7, 7.4 ± 0.7, 5.1 ± 0.7, and 7.1 ± 0.8 kg at 1, 2, 4, and 10 years, respectively, were significantly greater than the 1-kg weight loss at 1, 2, and 4 years and 3.5 ± 0.8 kg weight loss at 10 years for the DSE group (P values ≤ 0.0001). AHI was lower with ILI than DSE by 9.7, 8.0, and 7.9 events/h at 1, 2, and 4 years, respectively (P values ≤ 0.0004), and 4.0 events/h at 10 years (P = 0.109). Change in AHI over time was related to amount of weight loss, baseline AHI, visit year (P values < 0.0001), and intervention independent of weight change (P = 0.01). OSA remission at 10 years was more common with ILI (34.4%) than DSE (22.2%). Conclusions: Participants with OSA and type 2 diabetes mellitus receiving ILI for weight loss had reduced OSA severity at 10 years. No difference in OSA severity was present between ILI and DSE groups at 10 years. Improvement in OSA severity over the 10-year period with ILI was related to change in body weight, baseline AHI, and intervention independent of weight change.